PEMANFAATAN METODE AERASI DALAM PENGOLAHAN LIMBAH BERMINYAK - Arsawan, Made; Budiarsa Suyasa, I Wayan; Suarna, Wayan (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 2 No 2, 2012)
Oily waste can pollute environment. One of the method used to process the oily waste is aerationmethod. This researce is carried out by taking oily waste PT. Indonesia Power Business Unit Electric PowerStation Bali at Pasanggaran Denpasar, aimed at increase quality of the waste.The sampel used is waste of PT. Indonesia Power Electric Power Station Business Unit of Bali. Thesampel is intercepted and retained in a retaining box, and 11,12 litters are then taken to be put intotreatment tank. Aeration treatment duration given varies, such as 12 hours, 24 hours, 48 hours, and 72 hoursfor the sampel with air flow speed of 0,6m/s. The treatment is also done with adding sampel with mud of 1%of the whole sampel volume. The relation between Aerating duration with oil contents, oil layer, BOD value,COD value, TDS value and TSS value will be analyzed with simple correlation and descriptive analysis.Aeration treatment can reduce the contents of oil in waste and separate oil accumulated in the waterso that the oil can be depressed up. Aeration treatment can also lower BOD value, COD value, TDS valueand TSS value because giving oxygen in to waste will meet the needs of oxygen of disentanglingmicroorganism in the waste water and the needs of oxygen for oxidation of chemicals in the waste.Therefore, aeration treatment can increase quality of the waste.
Keywords: Aeration, Processing, Oily Waste